Company Valuation Analysis on PT Dayamitra Telekomunikasi in Preparation of Intial Public Offering (IPO) - Wahyudi, Andi; Surya, Budi Arta (The Indonesian Journal of Business Administration, 2013)
PT Dayamitra Telekomunikasi, known as Mitratel, a subsidiary of PT Telekomunikasi Indonesia Tbk, is a one of the leading company in tower leasing industry. In 2012 General Meeting of Shareholders, the shareholders asked Mitratel to explore the possibility of an IPO (Initial Public Offering). The objective of the shareholders is to unlock Mitratel value and to finance Mitratel capex while maintaining the Debt Equity Ratio (DER) below 4.0x. Mitratel must assess the value of the company and also asses the IPO plan itself. Undertaking an IPO is a business decision that must be based on consideration of a number of factors. The methods used in this final project to determine the value of Mitratel are Discounted Cash Flow (DCF) Valuation and Relative Valuation. DCF method used is two-stage Free Cash Flow to Equity (FCFE) Discount Model. Relative valuation methods used are Price to Earning Ratio (P/E) and Price to Book Value (PBV) multiples. The results from the two methods are combined to come up with the realistic and attractive price of equity per shares. This final project will also analyze the IPO decision based on strategic, financial, and valuation factors, whether the IPO will satisfy the objective of the shareholders. From the analysis, Mitratel is already eligible to list its shares in the main board of Indonesia Stock Exchange, with the recommended price for Mitratel equity is between Rp. 15.000,- to Rp. 20.000,- per share. However from the strategic, financial, and valuation analysis, in order to get better value, Mitratel is recommended to hold the IPO plan.Â Keywords: Two-stage Free Cash Flow to Equity Discount Model, Relative Valuation